An Ink-Jet Printed Eddy Current Position Sensor - Goran Stojanović; Nikola Bednar; Nikola Jeranče (Sensors, 2013)
An eddy current sensor with an ink-jet printed flexible inductor has been designed and fabricated. The inductor has been designed by means of software developed in-house. It has been fabricated by ink-jet printing with silver ink on a flexible substrate. The inductor is a part of the oscillator circuit whose oscillating frequency is measured by a microcontroller. The sensor characteristics have been analyzed for two types of application. The first considered application is the displacement of a large conductive target in a direction perpendicular to the inductor plane. The second considered application is the displacement of a small steel ball parallel to the inductor plane. Inductance and oscillating frequency have been measured in order to completely characterize the sensor. The obtained results validate the use of the sensor for both considered applications, and are in good agreement with the simulations. The advantages of this type of sensor are low cost, the possibility for the inductor to match any curved surface and flexibility and precision of the inductor design.